2012
DOI: 10.1155/2012/873892
|View full text |Cite
|
Sign up to set email alerts
|

Preferences for Advance Directives in Korea

Abstract: Background. The goal of advance directives is to help patients retain their dignity and autonomy by making their own decisions regarding end-stage medical treatment. The purpose of this study was to examine preferences of advance directives among general population in Korea. Method. A descriptive cross-sectional survey was performed from October 2007 to June 2008 in Seoul, Korea. A total of 336 city-dwelling adults self-administered the questionnaire and returned it via mail. Data analyses were conducted using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 27 publications
1
22
1
Order By: Relevance
“…30 In accordance with tradition, the eldest son or daughter is obliged by filial piety to do everything to prolong the older person's life, the opinions of family members and health care professionals take precedence over personal opinions or preferences. 31 In terms of preferred place of dying, 10 years ago, Liu and Gu 32 reported that nearly 90% of Chinese decedents older than 80 died at home, whereas our study found that fewer than a quarter (23.1%) wanted to die at home. The increasing number of single households in mainland China and fewer households comprising more than 1 generation means that fewer older people have access to the necessary family caregiver support to be able to die at home.…”
Section: End-of-life Care Preferences Among Nursing Home Residentscontrasting
confidence: 61%
“…30 In accordance with tradition, the eldest son or daughter is obliged by filial piety to do everything to prolong the older person's life, the opinions of family members and health care professionals take precedence over personal opinions or preferences. 31 In terms of preferred place of dying, 10 years ago, Liu and Gu 32 reported that nearly 90% of Chinese decedents older than 80 died at home, whereas our study found that fewer than a quarter (23.1%) wanted to die at home. The increasing number of single households in mainland China and fewer households comprising more than 1 generation means that fewer older people have access to the necessary family caregiver support to be able to die at home.…”
Section: End-of-life Care Preferences Among Nursing Home Residentscontrasting
confidence: 61%
“…34,35 Because the concept of advance directives has only been discussed nationwide in recent years, Korean people might not yet be familiar with the concept. 36 Education concerning advance directives for family members and health-care providers is needed for routine EOL care in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In 1 study, patients provided reasons for completing an AD, which included the desire to state one's treatment preferences, appoint proxy decision makers in the event that one may be unable to make decisions regarding end-of-life medical treatments, or make decision making by proxies easier; reasons for not completing an AD included lack of or insufficient knowledge of ADs, lack of understanding of the need for ADs, or uncomfortable having end-of-life discussions, including life support. 15 Nonetheless, most communitydwelling Korean people reported a preference for ADs over life-sustaining treatments 7,8 ; in particular, cardiopulmonary resuscitation or intravenous or tube feeding was undesirable in more than 60% of participants when these extended life rather than improved the condition. 7 In the United States, 80% of patients with chronic disease also reported that they were likely to avoid intensive treatments during hospitalization at the end of life.…”
Section: Public and Professional Education On Ad Knowledgementioning
confidence: 99%
“…15 Nonetheless, most communitydwelling Korean people reported a preference for ADs over life-sustaining treatments 7,8 ; in particular, cardiopulmonary resuscitation or intravenous or tube feeding was undesirable in more than 60% of participants when these extended life rather than improved the condition. 7 In the United States, 80% of patients with chronic disease also reported that they were likely to avoid intensive treatments during hospitalization at the end of life. 28 Health care professionals also reported challenges in decisions regarding end-of-life care and difficulty having such discussions with patients and families and assisting them in easy-to-understand advance care planning.…”
Section: Public and Professional Education On Ad Knowledgementioning
confidence: 99%
See 1 more Smart Citation